Using Mac OS X Mavericks - Wilson, Kevin (Kevin Peter) (Apress, 2014)
Using Mac OS Mavericks is the essential guide to using a computer running Mavericks, providing a complete resource for both the beginner and the enthusiast. Techniques are step-by-step using photography and screen prints throughout, together with concise, easy to follow text from an established expert in the field, provide a comprehensive guide to Apple Macs. Whether you have just bought your first Mac, switched from Windows, or are a keen computer user, this book will provide you with a firm grasp of the underpinning foundations and equip you with the skills needed to use a Mac like a pro.